Insights into the meridional ornamentation of the planktonic foraminiferal genus Rugoglobigerina (Late Cretaceous) and implications for taxonomy - F. Falzoni; M.R. Petrizzo; B. T. Huber; K. G. MacLeod (Cretaceous Research, 2014)
Wall texture and ornamentation in Cretaceous planktonic foraminifera, as with modern and Cenozoic taxa, are generally considered to be genetically controlled and thus taxonomically significant. For instance, the iterative development of meridional ornamentation is a diagnostic criterion used to discriminate between the Santonian-early Campanian genus Costellagerina, and the Campanian-Maastrichtian genus Rugoglobigerina. An alternative ecophenotypic explanation for differences based on observed poleward decreases in meridional ornamentation has not been widely accepted largely due to absence of evidence.Our study of Rugoglobigerina specimens recovered at three mid-low latitude localities (Exmouth Plateau, eastern Indian Ocean; Shatsky Rise, northwestern Pacific Ocean; Eratosthenes Seamount, eastern Mediterranean) confirms that meridional ornamentation is a primary character of their tests, but development of this feature is highly variable throughout the geographic and stratigraphic distribution of the genus. Within assemblages of Rugoglobigerina, there is a continuous morphological range from specimens with well-developed costellae arranged in a meridional pattern to specimens with relatively short ridges that are randomly oriented to meridionally aligned. Stable isotope (δ13C and δ18O) analyses indicate that specimens showing a more strongly developed meridional ornamentation consistently yield higher δ13C values than co-occurring less ornamented morphotypes at each examined locality, whereas patterns in the δ18O values are site-dependent. Interpretation of these patterns is not simple and might be related to different controlling factors acting together or separately. Potential explanations for the differential development of the ornamentation include: (1) adaptation to different ecological niches within a population, (2) species-level genetic differences, (3) variation in metabolic rate or activity within individuals, and (4) changes in the seawater carbonate ion saturation through space and time, including ...